Endocervicosis in an Intramammary Lymph Node. (October 2022) - Jebakumar, Deborah; Asirvatham, Jaya Ruth
Benign müllerian inclusions are frequently encountered within infra-diaphragmatic locations such as pelvic lymph nodes, bladder, cervix and vagina. Supra-diaphragmatic müllerian inclusions, especially endocervicosis, are exceedingly rare. We report a case of endocervicosis within an intramammary lymph node in a 49-year-old woman. To the best of our knowledge, this is the second reported case.